Has the propensity to pay dividends declined? Evidence from the US banking sector - Shaojie Lai; Qing Wang; Jiangze Du; Shuwen Pi (Journal of Risk and Financial Management, 2021)
This article examines the propensity to pay dividends in the U.S banking sector during 1973-2014. Although the propensity to pay dividends has been declining over the 52 years of our sample period, banks are consistently more likely to pay dividends than non-financial firms. Using the coefficients from logit models estimated early in the sample period to forecast the percentage of dividend payers in each subsequent year, we conclude that there has been a decline in the likelihood of paying dividends in the banking sector. However, the decline started from a very high level as compared to that of the non-banking sectors. In addition, the variables taken from the non-financial firm literature do not explain the difference between the actual and expected percentage of dividend payers in the banking sector. We also conduct exploratory analyses with bank-specific variables. Although newly included variables are significantly related to the likelihood of paying dividends, they do not explain the declining propensity to pay dividends in the banking sector.
Keywords: 330; banks; dividends; payout policy